基于小波包和Teager能量算子的齿轮故障诊断研究 - 陈仕琦; 康敏; 傅秀清 (Jixie chuandong)
The signals of gearbox fault vibration are usually non-stationary,in order to effectively extract the characteristic parameters of failure signal,the method of signal characteristic parameter extraction based on wavelet packet denoise and nonlinear Teager energy operator is proposed.By using the constructed signal simulation,the feasibility of this method to extract the signal characteristic parameter is studied,and this method is successfully applied to the eccentric gear gearbox fault diagnosis,which demonstrate the effectiveness of this method to extract characteristic parameter of gear fault gearbox vibration signal.